Uma imers\~ao nas contas públicas brasileiras - Rodrigo Toledo Cabral Cota (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– There is a belief among Brazilians that the country pays too much tax and that this value does not return to society with the provision of good public services, that the state inefficiency coupled with corruption consumes the generated resources. However, the Brazilian society needs to fully understand the composition of public spending and its evolution over the past few years. This study, therefore, aims to show the evolution of public accounts between the years 2010 and 2015. The economic slowdown and the increase of mandatory expenditures led Brazil to a primary surplus of R 127 billion in 2011 to a R 115.7 billion deficit in 2015. And reverse the situation is not as simple, since cutting government spending is limited: according to the Budget Law Project 2017, 93.2% of the expenditures are mandatory or not likely to be skimped. An analysis of government spending shows that it is time for society as a whole to discuss the problem and, from the knowledge of the composition and the evolution of public accounts, agree on a new standard distribution of their social resources.
Keywords: H50; H83; E62; 330; public accounts; public debt; fiscal adjustment